Probe Molecule-Dependent Particle Density and its Effect on the Supercritical Gas Adsorption Isotherm of Nanoporous Cu Complex Crystals - Hiroshi Noguchi; Atsushi Kondo; Hiroshi Kajiro; Hirofumi Kanoh; Katsumi Kaneko (Adsorption Science & Technology)
Accurate particle densities of the Cu-based metal organic framework [Cu(4,4'-bipyridine) 2 (BF 4 ) 2 ] for He, N 2 and CH 4 molecules using the high-pressure buoyancy method have been determined. A smaller probe molecule gave a larger particle density (1.70 g/ml from He, 1.66 g/ml from N 2 , 1.60 g/ml from CH 4 ). The effect of particle density on the evaluation of the surface excess mass for supercritical gas adsorption was examined; the above particle density difference gave rise to a 2–4% difference in the surface excess mass.